STRUCTURE AND EVOLUTION OF THE GLUECKSTADT GRABEN DUE TO SALT MOVEMENTS - Maystrenko Y.; Bayer U.; Scheck-Wenderoth M. (My University, 2005)
The salt tectonics of the Glueckstadt Graben has been investigated in relation to major tectonic events within the basin. The lithologic features of salt sections from Rotliegend, Zechstein and Keuper show that almost pure salt is prominent in the Zechstein, dominating diapiric movements that have influenced the regional evolution of the Glueckstadt Graben. Three main phases of growth of the salt structures have been identified from the analysis of the seismic pattern. The strongest salt movements occurred at the beginning of the Keuper when the area was affected by extension. This activation of salt tectonics was followed by a Jurassic extensional event in the Pompeckj Block and Lower Saxony Basin and possibly in the Glueckstadt Graben. The Paleogene–Neogene tectonic event caused significant growth and amplification of the salt structures mainly at the margins of the basin. This event was extensional with a possible horizontal component of the tectonic movements. 3D modelling shows that the distribution of the initial thickness of the Permian salt controls the structural style of the basin, regionally. Where salt was thick, salt diapirs and walls formed and where salt was relatively thin, simple salt pillows and shallow anticlines developed.
Keywords: Glueckstadt Graben